Experimental investigation of wave-induced morphological changes of gravel beaches - Atladottir, Audur (University of Ottawa (Canada), 2008)
Gravel beaches are widespread around the North-Atlantic Ocean shorelines and can also be found along the coastlines of New Zealand, Russia and the Pacific shore of USA. Over the past decades, researchers in coastal morphodynamics have placed their emphasis on studying sand beaches but gravel material is being used more frequently to nourish eroding sand beaches. The present thesis aims to advance the understanding of the behaviour of gravel beaches under wave attack. A two-dimensional physical model was developed for gravel beach applications. Regular and irregular waves were considered as well as two different initial beach slopes. An extensive analysis was performed on the time history of the waves, beach morphology, wave reflection and energy dissipation. Additional geotechnical analysis was also performed in order to identify the characteristics of the beach material. Wave height, wave period, wave duration and initial beach slope were all found to influence beach deformation and wave reflection pattern.
Keywords: Engineering, Civil.